Gender Versus Marital Concerns: Does 1 Corinthians 11:2-16 Address the Issues of Male/Female or Husband/Wife? - Massey, Preston T. (Tyndale bulletin, 2013)
This study proposes an alternative for interpreting the background to 1 Corinthians 11–14. The investigation will focus on the following three issues: 1) the issue of married women versus any woman; 2) the matter of a married woman’s talking in a public setting; and 3) the nature of the church as the family of God meeting in a house for public worship. The combination of these factors will lead to the conclusion that Paul is addressing marital issues.